Replication of Reduced Pattern Electroretinogram Amplitudes in Depression With Improved Recording Parameters - Friedel, Evelyn B. N.; Tebartz van Elst, Ludger; Schmelz, Céline; Ebert, Dieter; Maier, Simon; Endres, Dominique; Runge, Kimon; Domschke, Katharina; Bubl, Emanuel; Kornmeier, Jürgen; Bach, Michael; Heinrich, Sven P.; et al. (Frontiers in Medicine, 2021)
Background: The retina has gained increasing attention in non-ophthalmological research in recent years. The pattern electroretinogram (PERG), a method to evaluate retinal ganglion cell function, has been used to identify objective correlates of the essentially subjective state of depression. A reduction in the PERG contrast gain was demonstrated in patients with depression compared to healthy controls with normalization after remission. PERG responses are not only modulated by stimulus contrast, but also by check size and stimulation frequency. Therefore, the rationale was to evaluate potentially more feasible procedures for PERG recordings in daily diagnostics in psychiatry. Methods: Twenty-four participants (12 patients with major depression (MDD) and 12 age- and sex-matched healthy controls) were examined in this pilot study. We investigated PERG amplitudes for two steady-state pattern reversal frequencies (12.5 rps/18.75 rps) and four sizes of a checkerboard stimulus (0.8°, 1.6°, 3.2° and 16°) to optimize the PERG recordings in MDD patients. Results: Smaller PERG amplitudes in MDD patients were observed for all parameters, whereby the extent of the reduction appeared to be stimulus-specific. The most pronounced decline in the PERG of MDD patients was observed at the higher stimulation frequency and the finest pattern, whilst responses for the largest check size were less affected. Following the PERG ratio protocol for early glaucoma, where similar stimulus dependent modulations have been reported, we calculated PERG ratios (0.8°/16°) for all participants. At the higher frequency (18.75 rps), significantly reduced ratios were observed in MDD patients. Conclusion: The “normalization” of the PERG responses – via building a ratio – appears to be a very promising approach with regard to the development of an objective biomarker of the depressive state, facilitating inter-individual assessments of PERG recordings in patients with psychiatric disorders.